2008
DOI: 10.1128/mcb.02214-07
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Vascular Endothelial Growth Factor C (VEGF-C) and VEGF-D Is Not Equivalent to VEGF Receptor 3 Deletion in Mouse Embryos

Abstract: Lymphatic vessels play an important role in the regulation of tissue fluid balance, immune responses, and fat adsorption and are involved in diseases including lymphedema and tumor metastasis. Vascular endothelial growth factor (VEGF) receptor 3 (VEGFR-3) is necessary for development of the blood vasculature during early embryogenesis, but later, VEGFR-3 expression becomes restricted to the lymphatic vasculature. We analyzed mice deficient in both of the known VEGFR-3 ligands, VEGF-C and VEGF-D. Unlike the Veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 39 publications
11
168
1
1
Order By: Relevance
“…The generation of K14-VEGF-A Tg mice that express mouse VEGF-A164 under control of the K14 promoter, of K14-VEGF-C Tg mice that express human VEGF-C, and of K14-VEGF-D Tg mice that express mouse VEGF-D has been described previously Detmar et al, 1998;Xia et al, 2003;Haiko et al, 2008). K14-VEGF-A, K14-VEGF-C, and K14-VEGF-D Tg mice (all FVB genetic background) were bred and housed in the animal facility of ETH Zurich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of K14-VEGF-A Tg mice that express mouse VEGF-A164 under control of the K14 promoter, of K14-VEGF-C Tg mice that express human VEGF-C, and of K14-VEGF-D Tg mice that express mouse VEGF-D has been described previously Detmar et al, 1998;Xia et al, 2003;Haiko et al, 2008). K14-VEGF-A, K14-VEGF-C, and K14-VEGF-D Tg mice (all FVB genetic background) were bred and housed in the animal facility of ETH Zurich.…”
Section: Methodsmentioning
confidence: 99%
“…K14-VEGF-A+C and K14-VEGF-A+D double Tg mice were generated by crossing homozygous VEGF-A and hemizygous VEGF-C or VEGF-D Tg mice, respectively. The mice were genotyped as previously described Haiko et al, 2008). Untreated FVB wild-type mice were used as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Haiko et al investigated a mutant mouse model in which the mutation site was located downstream of the VEGFR-3 gene. The results revealed that dysgenopathy of lymphatic vessels in Vegfc +/-mice was ameliorated after Kemurinein 14 promoters induced the overexpression of the human or mouse VEGF-D gene in the mice (19). Therefore, the VEGF-C/VEGF-D/VEGFR-3 signaling pathways play an important role in the regulation of the tumor lymphangiogenesis process.…”
Section: Vegf-c and Vegf-d Vegf-c Or Vegf-d Combinesmentioning
confidence: 97%
“…Currently, the VEGF-C/VEGF-D/ VEGFR-3 signaling pathways are believed to be the most important mechanism underlying tumor lymphangiogenesis (16)(17)(18)(19)(20)(21)(22).…”
Section: Molecular Mechanism Of Tumor Lymphangiogenesismentioning
confidence: 99%
“…As mice deWcient in both Vegfc and Vegfd, unlike Vegfr3 null mice, have normal blood vascular development (Haiko et al 2008), it is likely that other VEGFR-3 ligands, such as integrins, contribute to VEGFR-3 signaling in blood vascular endothelium. Additional VEGF-C signal transduction pathways were also described, such as interaction of VEGF-C with neuropilin-2 (NP2) and integrin 9.…”
Section: Lymphatic Sproutingmentioning
confidence: 99%